Postwar : a history of Europe since 1945 - Judt, Tony 1948-2010 (The Penguin Press, 2005)
The first truly European history of contemporary Europe, from Lisbon to Leningrad, based on research in six languages, covering 34 countries across 60 years, using a great deal of material from newly available sources. The book integrates international relations, domestic politics, ideas, social change, economic development, and culture--high and low--into a single grand narrative. Every country has its chance to play the lead, and although the big themes are handled--including the cold war, the love/hate relationship with America, cultural and economic malaise and rebirth, and the myth and reality of unification--none of them is allowed to overshadow the rich pageant that is the whole.--From publisher description